(untitled) (Scientific journal of the Fergana State University, 2023)
In this work, one method of a partition of the given angle into three equal part, which is differ from the Archimed’s method, has been described. In every step we paid attention to that all actions done using only compass and ruler with two dots. In order to visualize and to show that it is possible to draw, the hand-made picture has been attached.